TRANSFORMATION THREE-DIMENSIONAL INTEGRALS - LIŠKA, Vladimír (Trends in education, 2011)
Substitution Method to multidimensional integrals is a powerful tool for calculating them, but its routine application can lead to lengthy calculations. This fact presents the example of three-dimensional integral, where the fundamental field is cone with its axis of symmetry o z .
Keywords: three-dimensional integral; Theorem of Fubini; cylindrical coordinates.